Geodynamic modeling on continental collision in Qilian orogenic belt - Zhou, Hui; Qing, Jiarong; Qi, Rui; Huang, Xingfu; Liao, Jie; Gao, Rui (Frontiers in Earth Science, 2024)
The Qilian orogenic belt (QOB) located in the northeast margin of the Tibetan Plateau is featured by remarkable crustal thrusting and shortening, providing a key natural example to understand the lithospheric deformation of the Tibetan Plateau. Two types of continental collision are observed in the QOB: lithosphere subduction beneath Southern Qilian and crust underthrusting of Alxa terrain along the North Border Thrust (NBT). Deep seismic reflection profiles reveal complex stress field evolution, including compressional deformation in the lower crust, extensional deformation in the upper crust, and detachment deformation in the middle crust. In this study, we use 2D numerical modeling to investigate the dynamics of these two different collision types and the evolution of Qilian uplift. Model results suggest three patterns of continental collision, i.e., crust underthrusting follows lithosphere subduction, lithosphere subduction and the failed underthrusting/subduction. The key factors that may influence model evolution, including crustal rheology, convergence direction and rate, are systematically investigated. Our model results are further compared to observations, suggesting that lower convergence rate and crust underthrusting along NBT likely control the uplift and crust stress stratification of the QOB.